Human Habitats (Urban & Social Environment) - Falk, Louise, author 648094 (Delhi, India : White Word Publications, 2012)
A house is a home, building or structure that is a dwelling or place for habitation by human beings. The term house includes many kinds of dwellings ranging from rudimentary huts of nomadic tribes to free standing individual structures. In some contexts, "house" may mean the same as dwelling, residence, home, abode, lodging, accommodation, or housing, among other meanings. The social unit that lives in a house is known as a household. Most commonly, a household is a family unit of some kind, though households can be other social groups, such as single persons, or groups of unrelated individuals. Settled agrarian and industrial societies are composed of household units living permanently in housing of various types, according to a variety of forms of land tenure. English-speaking people generally call any building they routinely occupy "home" Many people leave their houses during the day for work a recreation, and return to them to sleep and for other activities. House derives directly from Old English Hus meaning' Dwelling, shelter, house, "which in turn derives from Proto-Germanic Khusan (reconstructed by etymological analysis) which is of unknown origin.